Pattern of Partai Solidaritas Indonesia Candidacy In the Selection of DPRD DKI Jakarta Member Candidates In 2024’s General Election - Ida Bagus Gede Randika Pradayana; Ahmad Zaki Fadlur Rohman (Universitas Warmadewa, 2024)
This study discussed about the pattern of PSI candidacy in candidates selection for DPRD DKI Jakarta member in 2024’s General Election. This study was motivated because PSI can implementing high degree of participation in their candidacy process. That’s mean the candidacy process of PSI not only an area for elite but also all of the voters. That behavior, has been shown by PSI in the midst of political party situation which trapped in pragmatism. The method of this study is qualitative research with case study research type. Simultaneously, the theory which used in this study is Candidacy Theory who proposed by Gideon Rahat and Reuven. Y Hazan. The result of this study shown that the pattern of PSI candidacy is at a democratic level. It’s said democratic because PSI is able to act inclusively both in nominating candidates and candidates selection process. PSI doesn’t set the special requirements which difficult to fulfill, the PSI’s selectorate involves all of the voters, and the candidates selection is not only an area for a elite. Even though, the candidates nominations seems exclusive, but the most important of inclusive determination is voters involvement in candidacy process.